2017
DOI: 10.1093/humrep/dex275
|View full text |Cite
|
Sign up to set email alerts
|

Women's career priority is associated with attitudes towards family planning and ethical acceptance of reproductive technologies

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Lack of a stable partner, financial reasons, self‐realization and career status are some of the factors that influence a woman's decision to delay having children. Indeed, a recent study showed that career‐focused women place more value on intentional pregnancy planning to postpone childbearing, and have more confidence in assisted reproductive technology to counteract age‐related fertility decline, than those who do not place as much importance on career success . Female fertility decreases gradually at first, but significantly after the age of 35 years, which inevitably compromises fertility over time.…”
Section: Indications For Fertility Preservationmentioning
confidence: 99%
“…Lack of a stable partner, financial reasons, self‐realization and career status are some of the factors that influence a woman's decision to delay having children. Indeed, a recent study showed that career‐focused women place more value on intentional pregnancy planning to postpone childbearing, and have more confidence in assisted reproductive technology to counteract age‐related fertility decline, than those who do not place as much importance on career success . Female fertility decreases gradually at first, but significantly after the age of 35 years, which inevitably compromises fertility over time.…”
Section: Indications For Fertility Preservationmentioning
confidence: 99%
“…The same procedure has been used to cryopreserve oocytes, but the challenges have been much greater on account of their physical characteristics. Evidence of safety for children born from vitrified oocytes after IVF and standardization of the technique allowed oocyte cryopreservation to no longer be considered experimental (Hammarberg et al ., 2017; Simoni et al ., 2017; Noyes et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, continuous and face-to-face education regarding the age-related risks of pregnancy is required to improve their health literacy [40]. It is also believed that individuals’ values may directly impact behaviors related to reproductive health [41]; however, the effect of personal values and being informed and encouraged about the timing of pregnancy during young adulthood needs further longitudinal evaluations [42].…”
Section: Discussionmentioning
confidence: 99%
“…Social and educational institutions need to become more pregnancy-friendly to encourage women to have an early pregnancy [45]. In addition, women will benefit from increased support in the workplace and from insurance systems for fertility preservation and healthy reproduction [41].…”
Section: Discussionmentioning
confidence: 99%